Portuguese Institutions’ Strategies and Challenges to Attract International Students: External Makeover or Internal Transformation? - Sin, Cristina; Tavares, Orlanda; Cardoso, Sónia (Journal of International Students, 2019)
Public institutions in Portugal have not invested in strategies to attract international students until recently, when the adoption of new legislation and a national strategy for internationalization created more appealing conditions for it. This article aims to study the strategies institutions employ to recruit international students in a country less attractive than the major receiving countries and the main challenges they encounter. The study draws on interviews with top and middle managers in two public universities. The findings identify three types of strategies: institutional branding, revision of admission procedures, and curricular adjustments. The main challenges are the creation of institutional structures with an exclusive remit for international students and the choice of teaching language, despite a prevailing opinion that the Portuguese language should be maintained as a competitive advantage.